Synthesis and Characterization of Ti-Nb Alloy Films Obtained by Magnetron Sputtering and Low-Energy High-Current Electron Beam Treatment; Mathematics; Vol. 14, iss. 12 - Morini F. Federico; Bestetti M. Massimiliano; Franz S. Silvia; Vicenzo A. Antonello; Markov A. B. Aleksey Borisovich; Yakovlev E. A. Evgeny Aleksandrovich (2021, 2021)
Title screen